Differential growth at the apical hook: all roads lead to auxin - Abbas, Mohamad; Alabadí, David; Blázquez, Miguel A. (Frontiers in Plant Science, 2013)
The apical hook is a developmentally regulated structure that appears in dicotyledonous seedlings when seeds germinate buried in the soil. It protects the shoot apical meristem and cotyledons from damage while the seedling is pushing upwards seeking for light, and it is formed by differential cell expansion between both sides of the upper part of the hypocotyl. Its apparent simplicity and the fact that it is dispensable when seedlings are grown in vitro have converted the apical hook in one of the favorite experimental models to study the regulation of differential growth. The involvement of hormones –especially auxin– in this process was manifest already in the early studies. Remarkably, a gradient of this hormone across the hook curvature is instrumental to complete its development, similar to what has been proposed for other processes involving the bending of an organ, such as tropic responses. In agreement with this, other hormones –mainly gibberellins and ethylene–, and the light, regulate in a timely and interconnected manner the auxin gradient to promote hook development and its opening, respectively. Here, we review the latest findings in the field, paying special attention to the molecular mechanisms for the cross-regulation between the different hormone signaling pathways that underlie this developmental process.